Perches help birds to kill pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Perches are attracting insect eating birds to crops of groundnut in India. A farmer in the coastal regions of Andhra Pradesh has found that by making it easier for birds to spot insects in his crop he is able to reduce his need for chemical...